Exploring the Link between Maternal Weight Gain During Pregnancy and LBW Incidence Amid COVID-19 - Metty Tsabitah Aziz; Anjarwati (The Indonesian Institute of Science and Technology Research, 2023)
The highest mortality cause in Indonesia is low birt weight (LBW). One of LBW causal factors is mothers’ lack of weight during pregnancy. Covid-19 pandemic affects all aspects including economy which economy which causes the unfulfilled nutrition needs in pregnant women. The objective of the study is to analyze the relation of mother’s weight rise during pregnancy and LBW incidents in the time of Covid-19 pandemic at Titik Kurniati private midwifery clinic. The study was a quantitative one with cross sectional design. The samples of the study were 64 samples taken by using quota sampling. The study used secondary data taken from medical and birth registration records. The data analysis used in the study was ficher exact. The study result showed p value of 0.002 and OR value was 16.44 (95% CI: 1.90-141.71). There is a significant relation of mother’s weight during pregnancy and LBW incidents in the time of Covid-19 pandemic period at Titik Kurniati private midwifery clinic. Mothers with abnormal body weight during pregnancy have 16 times higher risk to give birth in LBW condition compared with mothers with normal body weight during pregnancy.